Use of oral contraceptives to manipulate menstruation in young, physically active women - Schaumberg, M.; Emmerton, Lynne; Jenkins, D.; Burton, N.; de Jonge, X.; Skinner, T. (Human Kinetics, 2017)
Purpose: Menstruation and menstrual symptoms are commonly-cited barriers to physical activity in women. The delay or avoidance of menstruation through extended oral contraceptive regimens may mitigate these barriers, yet information on menstrual manipulation practices in young physically-active women is sparse. The objective of this study was to investigate prevalence of, and reasons for, menstrual manipulation with oral contraceptives in recreationally- and competitively- active women. Methods: 191 recreationally-active (self-reported moderate-to-vigorous physical activity 150-300 min.week-1) women (aged 23±5 years), 160 sub-elite recreationally-active (self-reported moderate-to-vigorous physical activity >300 min.week-1) and 108 competitive (state-, national- or international-level) athletes (aged 23±4 years) completed a self-administered questionnaire assessing oral contraceptive regimen habits and reasons for manipulation of menstruation. Results: The majority (74%) of oral contraceptive users reported deliberately manipulating menstruation at least once during the previous year, with 29% reporting manipulating menstruation at least four times. Prevalence of menstrual manipulation (at least once in the previous year) was not different between competitive athletes, sub-elite recreationally-active and recreationally-active women (77% vs. 74% vs. 72%; p>0.05).The most cited reasons for manipulating menstruation were special events or holidays (rated by 75% as important/very important), convenience (54%), and sport competition (54%). Conclusions: Menstrual manipulation through extended oral contraceptive regimens is common practice in recreationally- and competitively-active young women, for a range of reasons relating to convenience that are not limited to physical activity. This strategy may assist in reducing hormone related barriers to exercise participation, thereby positively impacting on participation and performance.